WORKSHOP DESIGN KONTEN PEMASARAN DIGITAL MENGGUNAKAN CANVA - Amrina, Uly; Oktora, Raden Adriyani (Universitas Sahid, 2023)
This community service activity was carried out in the form of a workshop by the implementing team from the Industrial Engineering Undergraduate Study Program, Faculty of Engineering, Mercu Buana University in collaboration with the Budi Andhika Selaras Foundation. The aim of this activity is to help provide knowledge and skills and train MSME business actors to be more creative and independent in creating interesting and effective Digital Marketing content. This activity method includes 3 stages, namely the preparation stage in the form of identifying target needs, the workshop implementation stage and the evaluation stage of activity results. This workshop activity uses the Canva application, which is a graphic design application that is user-friendly and easy to use, and is considered suitable for MSMEs. This application is practiced directly in the form of content creation training - content such as flyer content, leaflets, banners, promotional videos, etc. Participants who took part in this workshop were 26 MSME workers in the Cinere area in the fields of cosmetics, food, drinks and clothing. As a result of this activity, each participant was able to create marketing content using the Canva application with various designs produced. The evaluation results after the activity took place showed that all participants were satisfied and gave good appreciation to this workshop activity. This activity is expected to provide broad benefits, both academically and in improving the quality of MSMEs in Indonesia.